Atmospheric Aerosol Assisted Pulsed Plasma Polymerization: An Environmentally Friendly Technique for Tunable Catechol-Bearing Thin Films - Jalaber, Vincent; Del Frari, Doriane; De Winter, Julien; Mehennaoui, Kahina; Planchon, Sébastien; Choquet, Patrick; Detrembleur, Christophe; Moreno-Couranjou, Maryline (Frontiers in Chemistry, 2019)
In this work, an atmospheric aerosol assisted pulsed plasma process is reported as an environmentally friendly technique for the preparation of tunable catechol-bearing thin films under solvent and catalyst free conditions. The approach relies on the direct injection of dopamine acrylamide dissolved in 2-hydroxyethylmethacrylate as comonomer into the plasma zone. By adjusting the pulsing of the electrical discharge, the reactive plasma process can be alternatively switch ON (tON) and OFF (tOFF) during different periods of time, thus allowing a facile and fine tuning of the catechol density, morphology and deposition rate of the coating. An optimal tON/tOFF ratio is established, that permits maximizing the catechol content in the deposited film. Finally, a diagram, based on the average energy input into the process, is proposed allowing for easy custom synthesis of layers with specific chemical and physical properties, thus highlighting the utility of the developed dry plasma route.